ANALYSIS OF STUDENTS' THINKING STYLES IN READING FREE-BODY DIAGRAMS AND ANALYTICAL THINKING ON NEWTON'S LAWS - Soleha, Nikmatu; Fadly , Wirawan; David , Martinez (EduFisika: Jurnal Pendidikan Fisika, 2025)
Analytical thinking skills are essential for understanding and solving physics problems, particularly those involving Newton's Laws. One effective way to develop these skills is through the use of free-body diagrams. This study aims to analyze the influence of students’ thinking styles, Concrete Sequential, Abstract Sequential, Concrete Random, and Abstract Random on their analytical thinking abilities in interpreting free-body diagrams. Conducted using a qualitative descriptive approach at State Junior High School 1 Mlarak, Ponorogo Regency, data collection methods included observation, interviews, and document analysis. The findings reveal that students’ thinking styles significantly affect their ability to comprehend and represent forces in free-body diagrams. Students with a Concrete Sequential style demonstrated a more systematic approach in identifying and organizing forces, while those with an Abstract Random style faced greater challenges in structuring information. These results suggest that visual-based learning, such as the use of free-body diagrams, can enhance physics understanding and analytical thinking skills when aligned with students’ thinking styles. This study serves as an initial effort to support the development of students' analytical thinking skills, especially in the context of visual representation in physics. Additionally, the findings can be used by teachers as a reference for designing instructional strategies that cater to diverse thinking styles, thereby enriching the practice of physics education and promoting higher-order thinking skills.